PENANAMAN PENDIDIKAN AGAMA PADA ANAK SEJAK DALAM KANDUNGAN - Reflita, Reflita (IAIN Padangsidimpuan, 2013)
Educating children is an investment in early pregnancy. Because at the moment is the beginning of the formation of education where the age of 3 months and 10 days the baby has blown his spirit, It means that candidate baby has gained alive and has been educated . Even education on this age is very important because the child is very pitch of the sound around it, thus giving parents’ education will be implemented and will be equipped or recorded to be knowledge. After the child is born, the provision of continuing education will be easier received compared with those who have never been educated their children in the womb.